Association between socioeconomic status and arteriosclerotic cardiovascular disease risk and cause-specific and all-cause mortality: Data from the 2005–2018 National Health and Nutrition Examination Survey - Shen, Ruihuan; Zhao, Ning; Wang, Jia; Guo, Peiyao; Shen, Shuhui; Liu, Detong; Liu, Donghao; Zou, Tong (Frontiers in Public Health, 2022)
Background: Morbidity and mortality of arteriosclerotic cardiovascular disease (ASCVD) varied according to socioeconomic status (SES), and evidence on the association between SES and ASCVD risk, and cause-specific and allcause mortality was nevertheless lacking in large-scale or population-based studies. Methods: A multicycle cross-sectional design and mortality linkage study was conducted using data from Continuous National Health and Nutrition Examination Survey (NHANES) in the United States, including public use linked mortality follow-up files through December 31, 2019. Poverty income ratio (PIR) served as a SES index. A series of weighted Logistic regressions and Cox proportional hazards regressions were used to investigate the association between the SES and the risk of ASCVD and mortality, respectively. Results: The study sample was comprised of 30040 participants aged 20 to 85 years old during the 2005-2018 period. Weighted Logistic regression models consistently indicated significant relationship between people experiencing poverty and increased risk of ASCVD, and linear trend tests were all statistically significant (all P for trend < 0.001). Additionally, weighted Cox regression analysis consistently demonstrated that the hazards of cause-specific and allcause mortality increased, with the decrease of each additional income level, and trend analyses indicated similar results (all P for trend < 0.001). Conclusions: Our study confirmed that the SES was strongly linked to living with ASCVD, and cause-specific and allcause mortality, even after adjusting for other factors that could impact risk, such as the American Heart Association (AHA)’s Life's Simple 7 cardiovascular health score and variables of age, sex, marital status, education, and depression severity.